The Style Of The Celengan Dance In The Jaranan Art Performance In Kediri: The Style Of The Celengan Dance In The Jaranan Art Performance In Kediri - Agoes Moeryanto, Rahm Aprila; Juwariyah, Anik (Solah, 2025)
This research explores the style of Celengan dance within Jaranan performances in Kediri, East Java. Celengan dance represents the wild boar character, traditionally performed by male dancers with vigorous and aggressive movements. This study aims to describe the form, symbolic meaning, and role of Celengan dance in the context of Jaranan. Using a qualitative approach, data were collected through field observations, in-depth interviews with dancers, leaders of Jaranan groups, and literature review. The findings reveal that Piggy bank dance incorporates low postures, dynamic gestures, and expressive facial movements, representing characteristics of cunning, greed, and spontaneity. In contemporary performances, female dancers have also begun performing this role, contributing to a new interpretation of the Celengan character. This study highlights how the Piggy Bank dance not only serves as entertainment but also as a medium for symbolic expression and cultural preservation.